Deletion of ACLY Disrupts Histone Acetylation and IL-10 Secretion in Trophoblasts, Which Inhibits M2 Polarization of Macrophages: A Possible Role in Recurrent Spontaneous Abortion. (11th May 2022) - Chen, Xin; Song, Qian Lin; Li, Ze Hong; Ji, Rui; Wang, Jia Yu; Ge, Chang; Xiao, Zhuo Ni; Guo, Duan Ying; Yang, Jing
Abstract : Changes to macrophage polarization affect the local microenvironment of the placenta, resulting in pathological pregnancy diseases such as recurrent spontaneous abortion (RSA). Macrophages are in close contact with trophoblasts during placental development, and trophoblast-derived cytokines are important regulators of macrophage polarization and function. Histone acetylation can affect the expression and secretion of cytokines, and ATP citrate lyase (ACLY) is an important factor that regulates histone acetylation. The aim of this study was to investigate the effect of ACLY expression differences in trophoblast on macrophage polarization and its mechanism. Our data demonstrate that ACLY level in placental villi of patients with RSA is decreased, which may lead to the inhibition of histone acetylation in trophoblasts, thereby reducing the secretion of IL-10. Reduced IL-10 secretion activates endoplasmic reticulum stress in macrophages, thus inhibiting their M2 polarization.